PERANAN RESILIENSI SEBAGAI MODERATOR DALAM HUBUNGAN CAREER ADAPTABILITY DAN SELF-PERCEIVED EMPLOYABILITY PADA KARYAWAN GENERASI Z - Najla Nada Muslimah; Jolanda Chatarina Wibawa; Della Novita Sigalingging; Assyifa Hapsari Sya’ban Komarudin; Riana Sahrani (STKIP Subang, 2025)
This study aims to analyze the role of resilience as a moderator variable on the relationship between career adaptability and self-perceived employability in Generation Z employees. This study uses correlational quantitative research methods to determine the relationship between variables, with specific qualifications such as age range from 17 years to 28 years with work experience, resulting in 388 respondent data. The research instruments used were the Career Adapt-Abilities Scale (CAAS), Self-Perceived Employability Scale (SPES), and Resilience Scale (RS-14) which were translated and then distributed via google form. Data were analyzed using correlation and regression test between 2 variables with moderator on SPSS. The results showed that there is a positive and significant relationship between career adaptability and self-perceived employability with the moderation of resilience. That is, in Generation Z employees with high levels of resilience, the relationship between career adaptability and self-perceived employability becomes stronger. Resilience acts as a benchmark for the possibility of individuals to be more effective in Generation Z career adaptation.